2020
DOI: 10.3762/bjoc.16.210
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4-substituted azopyridine-functionalized Ni(II)-porphyrins as molecular spin switches

Abstract: We present the synthesis and the spin switching efficiencies of Ni(II)-porphyrins substituted with azopyridines as covalently attached photoswitchable ligands. The molecules are designed in such a way that the azopyridines coordinate to the Ni ion if the azo unit is in cis configuration. For steric reasons no intramolecular coordination is possible if the azopyridine unit adopts the trans configuration. Photoisomerization of the azo unit between cis and trans is achieved upon irradiation with 505 nm (trans→cis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Investigations revealed that introducing electron-withdrawing substituents at the porphyrin meso positions improves the coordination of the pyridine to the Ni ion. [121] Rational fully reversible and highly efficient on-off photoswitching of magnetic resonance imaging (MRI) contrast with green and violet-blue light was also achieved with these LD-CISSS active molecular magnetic switches. [29,119a] The relaxivity (R1) of the contrast agent changes by a factor of 6.7, which was clearly visible in a clinical MRI scanner.…”
Section: Controlling Magnetic Properties By Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations revealed that introducing electron-withdrawing substituents at the porphyrin meso positions improves the coordination of the pyridine to the Ni ion. [121] Rational fully reversible and highly efficient on-off photoswitching of magnetic resonance imaging (MRI) contrast with green and violet-blue light was also achieved with these LD-CISSS active molecular magnetic switches. [29,119a] The relaxivity (R1) of the contrast agent changes by a factor of 6.7, which was clearly visible in a clinical MRI scanner.…”
Section: Controlling Magnetic Properties By Lightmentioning
confidence: 99%
“…Since complex 66 (Figure 20) switch efficiently between dia‐ and paramagnetic states in homogeneous solutions, they can also be used as a molecular logic gate with light and pH as input and the magnetic state as a non‐destructive read‐out. Investigations revealed that introducing electron‐withdrawing substituents at the porphyrin meso positions improves the coordination of the pyridine to the Ni ion [121] . Rational fully reversible and highly efficient on–off photoswitching of magnetic resonance imaging (MRI) contrast with green and violet‐blue light was also achieved with these LD‐CISSS active molecular magnetic switches [29,119a] .…”
Section: Controlling Magnetic Properties By Lightmentioning
confidence: 99%
“…[35][36][37][38] As we have previously demonstrated, the axial coordination of metal and functional pyridines is a viable route to generate vertical electrical field to monolayer MoS2 thanks to different alignments and magnitudes of molecular dipoles (taking advantage of the confinement of crystal field of octahedral transition metal d-orbital of zinc and cobalt phthalocyanine). 21,[39][40][41] The method has also been proved recently for stable growth of larger p-conjugated pyridinic ligands. 42 Our previous observations revealed that the dipole-induced doping of axially-coordinated pyridines could attain 10 12 /cm 2 of charge carrier density change to MoS2, being comparable to traditional electron donor/acceptor molecules, ensuring a memory window of more than 20V on SiO2 dielectric.…”
mentioning
confidence: 99%
“…Several previous works showed that triazatriangulenium (TATA) ions on the surface could be an appropriate platform to bind azobenzene with ethinyl or phenyl spacers where the photoisomerization of freestanding azobenzene is observed by scanning tunneling microscopy (STM). ,, Recently, this class of molecule has been proven to enhance Raman signals and modulate the work functions of 2D materials. , However, production of the TATA platform requires a multistep cumbersome synthesis, whereas a thermodynamically driven approach based on molecular self-assembly would be more convenient. Among others, metal porphyrins and phthalocyanines are well-established molecular scaffolds that are usually flatly physisorbed on 2D materials and could also provide such functionality for growing axially bonded azobenzene ligands in a more versatile and modular manner. As we have previously demonstrated, the axial coordination of metal and functional pyridines is a viable route to generate a vertical electrical field to monolayer MoS 2 thanks to different alignments and magnitudes of molecular dipoles (taking advantage of the confinement of crystal field of octahedral transition metal d-orbital of zinc and cobalt phthalocyanine). , The method has also been proven recently for stable growth of larger π-conjugated pyridinic ligands . Our previous observations revealed that the dipole-induced doping of axially coordinated pyridines could attain 10 12 /cm 2 of the charge carrier density change to MoS 2 , being comparable to traditional electron donor/acceptor molecules, ensuring a memory window of more than 20 V on SiO 2 dielectric.…”
mentioning
confidence: 99%